Effect of color visual stimulation by colored glass lenses on postural control - Zhang, Wenyu; Takada, Hiroaki; Hettmannsperger, Manuel; Négyesi, János; Wang, Ziheng; Nagatomi, Ryoichi (Scientific reports, 2025)
Visually emotive stimuli modulate postural control via cognitive pathways, and while colored lenses alter emotional responses, their impact on postural control remains uncertain. Previous studies showed that individually optimized colored glasses enhanced reading performance. However, it remains unclear if these effects extend to postural control. This study aimed to examine the relationship between colors and postural control with colored lenses against a white background, hypothesizing that postural control may be affected by individually different colors. Twelve healthy adults performed a single-leg stance test on a force plate under 26 color conditions, with each condition repeated six times in a non-consecutive manner. Three color conditions with the smallest, 2nd smallest and 3rd smallest environmental area (ENV) of center of pressure (COP) changes in 10 s were individually selected as the participant’s best colors. Individual worst colors were selected as those with the largest, 2nd largest and 3rd largest ENV. COP changes in the front hop landing test were examined for the selected 6 color conditions with the transparent condition as a control. The average ENV of the selected best color was significantly smaller than the transparent condition, and that of the selected worst color was significantly larger than the transparent condition in the single-leg stance test. The best or worst colors were individually different, and there were no specific trends in colors or concentrations. The selected color conditions tested in the front hop test revealed that the worst colors had larger ENV than the transparent condition, but the best color conditions had no advantage in postural control. In conclusion, visual color conditions provided by colored lenses have significant impact on postural control both in favorable and unfavorable way, and the color conditions were individually different.
Gesehen am 15.08.2025